Proapoptotic and Antiangiogenic Activities of Arctium Lappa L. on Breast Cancer Cell Lines - Mohamad Taleb Agha; Hussein M. Baharetha; Majed Ahmed Al-Mansoub; Yasser M. Tabana; Nur Hidayah Kaz Abdul Aziz; Mun Fei Yam; Amin Malik Shah Abdul Majid (Scientifica)
In this study, the bioactivity-guided fractionation was conducted on the aerial parts of Arctium lappa L. and then the extracts were tested in vitro on breast cancer (MCF-7), colorectal cancer (HCT-116), and normal cells (EA.hy926). The n-hexane fraction (EHX) of the ethanolic extract showed strong activity against both MCF-7 and EA.hy926 cell lines (IC50 values: 14.08 ± 3.64 and 27.25 ± 3.45 μg/mL, respectively). The proapoptotic activity of EHX was assessed using MCF-7. Morphological alterations were visualized using Hoechst staining and a transmission electron microscope. Cancer cell signal transduction pathways were investigated, and EHX significantly upregulated p53, TGF-β, and NF-κB. Furthermore, EHX was found to disrupt the metastatic cascade of breast cancer cells by the inhibition of cell proliferation, migration, invasion, and colonization. The antiangiogenic activity of EHX fraction showed potent inhibition of rat aorta microvessels with IC50 value: 4.34 ± 1.64 μg/mL. This result was supported by the downregulation of VEGF-A expression up to 54%. Over 20 compounds were identified in EHX using GC-MS, of which stigmasterol, ß-sitosterol, and 3-O-acetyllupeol are the major active compounds. Phytochemical analysis of EHX showed higher phenolic and flavonoid contents with a substantial antioxidant activity. In conclusion, this work demonstrated that A. lappa has valuable anticancer activity and antiangiogenic properties that might be useful in breast cancer therapy.